AUDIT OPERASIONAL ATAS KLAIM PASIEN BPJS DI RUMAH SAKIT HP - I Wayan Alvin Kertanegara; Carmel Meiden (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Submission of claims to the BPJS Health is carried out every month by submitting documents for recapitulation of services and patient supporting files. Incomplete documents and delays in submitting claims can cause claims to be rejected, delayed and late to be billed. This can lead to disruption of the hospital's cash flow, which affects the high costs incurred and causes losses. To overcome this, proper management policies need to be implemented. Through this study, researchers want to analyze management policies on BPJS patient claims at rumah sakit HP in 2021. Data collection is carried out by documentation and interview. Data analysis is carried out by descriptive technique starting from a preliminary survey, testing of control, detailed testing, until report development. The results of the study indicate that there is a large difference in the cost of outpatient and inpatient claims between the total rate and the hospital rate which is a loss for the hospital. However, management's policy is considered capable of controlling costs and reducing this high loss by 10% to 20%.